Understanding structure-activity relationships in linear polymer photocatalysts for hydrogen evolution. Issue 1 (December 2018) - Sachs, Michael; Sprick, Reiner; Pearce, Drew; Hillman, Sam; Monti, Adriano; Guilbert, Anne; Brownbill, Nick; Dimitrov, Stoichko; Shi, Xingyuan; Blanc, Frédéric; Zwijnenburg, Martijn; Nelson, Jenny; et al.
Abstract Conjugated polymers have sparked much interest as photocatalysts for hydrogen production. However, beyond basic considerations such as spectral absorption, the factors that dictate their photocatalytic activity are poorly understood. Here we investigate a series of linear conjugated polymers with external quantum efficiencies for hydrogen production between 0.4 and 11.6%. We monitor the generation of the photoactive species from femtoseconds to seconds after light absorption using transient spectroscopy and correlate their yield with the measured photocatalytic activity. Experiments coupled with modeling suggest that the localization of water around the polymer chain due to the incorporation of sulfone groups into an otherwise hydrophobic backbone is crucial for charge generation. Calculations of solution redox potentials and charge transfer free energies demonstrate that electron transfer from the sacrificial donor becomes thermodynamically favored as a result of the more polar local environment, leading to the production of long-lived electrons in these amphiphilic polymers. While inorganic semiconductors are well-studied for their solar-to-fuel energy conversion abilities, organic materials receive far less attention. Here, authors prepare linear conjugated polymers as H2 evolution photocatalysts and rationalize photocatalytic activities with fundamental properties.